Mineralogical assemblages forming at hyperalkaline warm springs hosted on ultramafic rocks: A case study of Oman and Ligurian ophiolites. (31st July 2013) - Chavagnac, Valérie; Ceuleneer, Georges; Monnin, Christophe; Lansac, Benjamin; Hoareau, Guilhem; Boulart, Cédric
Abstract : [1] We report on the mineralogical assemblages found in the hyperalkaline springs hosted on Liguria and Oman ophiolites based on exhaustive X‐ray diffraction and scanning electron microprobe analyses. In Liguria, hyperalkaline springs produce a thin brownish calcite precipitate that covers the bedrock due to the concomitant atmospheric CO2 uptake and neutralization of the hyperalkaline waters. No brucite and portlandite minerals are observed. The discharge of alkaline waters in Oman ophiolite forms white‐orange precipitates. Calcium carbonate minerals (calcite and/or aragonite) are the most abundant and ubiquitous precipitates and are produced by the same mechanism as in Liguria. This process is observed as a thin surface crust made of rhombohedral calcite. Morphological features of aragonite vary from needle‐, bouquet‐, dumbbell‐, spheroidal‐like habitus according to the origin of carbon, temperature, and ionic composition of the hyperalkaline springs, and the biochemical and organic compounds. Brucite is observed both at hyperalkaline springs located at the thrust plane and at the paleo‐Moho. The varying mixing proportions between the surface runoff waters and the hyperalkaline ones control brucite precipitation. The layered double hydroxide minerals occur solely in the vicinity of hyperalkaline springs emerging within the bedded gabbros. Finally, the dominant mineralogical associations we found in Oman (Ca‐bearing carbonates and brucite) in a serpentinizing environment driven by the meteoric waters are surprisingly the same as those observed at the Lost City hydrothermal site in a totally marine environment. Key Points: Distinct mineralogical association between Oman and liguria alkaline springs There is no Mg‐bearing carbonate similar mineral assemblage in marine and surface serpentinizing environment